PENGARUH DOSIS EKSTRAK DAUN SIRIH (PIPER BETLE L.) TERHADAP PENINGKATAN DAN KEBERHASILAN DAYA TETAS TELUR IKAN MAS (Cyprinus Carpio) YANG DITETASKAN PADA SUHU 28⁰C - Yossy Amanda Pakpahan; Rosmaiti, Rosmaiti; Andika Putriningtia (Jurnal Cakrawala Ilmiah, 2024)
Goldfish (Cyprinus carpio) is one of the prima donna of the freshwater fishery zone. In the market, this fish has a large low price and a fairly high demand, especially in the local market in Indonesia. The high demand for goldfish as a consumption need. One of the efforts to increase goldfish production in order to meet market demand is to develop a goldfish farming business. Unfertilized eggs are often attacked by microbes or disease-causing organisms that prevent the eggs from hatching and attempts are made to eradicate the microbes. This study aims to determine the appropriate dose of betel leaf extract in increasing egg hatchability and survival of goldfish larvae. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments with 3 replications. This treatment provided different doses of betel leaf extract, namely control (P1), 1.25 ml (P2), 1.50 ml (P3), 1.75 ml (P4). The observed parameters were the percentage of egg hatchability, abnormalities and survival rates. The results showed that administration of betel leaf extract had a significant effect on egg hatchability and goldfish survival rate. Whereas on the abnormality of carp larvae, betel leaf extract had no significant effect. The highest percentage of egg hatchability was P2 at 60%, the best percentage of larval abnormalities was obtained at P1, namely 0%, and the highest percentage of survival rate was at P2, namely 95.25%.